2009
DOI: 10.1292/jvms.71.1089
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Granulomatous Pleuropneumonia Associated with Actinobacillus pleuropneumoniae Serotype 2 in Slaughter Pigs

Abstract: ABSTRACT. A total of 14,818 slaughtered pigs were examined macroscopically. Of these, 25 pigs with porcine pleuropneumonia were collected and the relations among Actinobacillus spp. and granulomatous lesions in organs (lungs and tonsils) were evaluated. In the lungs, only Actinobacillus pleuropneumoniae serotype 2 was isolated from 20 of the pigs. Histologically, granulomatous pneumonia with A. pleuropneumoniae antigen was detected in 8 of the pigs. The antigen was visible in the centers of the lesions along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Other lesions have been described only occasionally. They include meningitis and nephritis due to A. pleuropneumoniae serovar 6 [ 11 ], multifocal granulomatous hepatitis [ 17 ], granulomatous lymphadenitis [ 15 ], osteomyelitis and arthritis [ 8 ] due to A. pleuropneumoniae serovar 2, and pericarditis [ 1 ] due to A. pleuropneumoniae serovars 1 and 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other lesions have been described only occasionally. They include meningitis and nephritis due to A. pleuropneumoniae serovar 6 [ 11 ], multifocal granulomatous hepatitis [ 17 ], granulomatous lymphadenitis [ 15 ], osteomyelitis and arthritis [ 8 ] due to A. pleuropneumoniae serovar 2, and pericarditis [ 1 ] due to A. pleuropneumoniae serovars 1 and 2.…”
mentioning
confidence: 99%
“…Recently, Ohba et al have reported the formation of asteroid bodies (also known as Splendore-Hoeppli reaction) with bacterial clumps of A. pleuropneumoniae serovar 2 in granulomatous lesions of the lung, liver, spleen and lymph node of slaughter pigs in Japan [ 15 , 16 , 17 ]. However, there are no reports on the formation of asteroid bodies in pigs experimentally infected, or in the acute and subacute cases of pigs naturally infected with A. pleuropneumoniae [ 2 , 12 , 18 , 20 ].…”
mentioning
confidence: 99%
“…In the event of an acute outbreak of App, it can be treated with tilmicosin injection (Papatsiros et al, ), but if it occurs on a large scale, the injection will greatly increase the cost and require a large amount of labour. Pigs are often chronically infected and App is detected at slaughter (Ohba et al, ). Therefore, it is the most economical and feasible way to mix drugs and feed, or to put them in water.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs die quickly after App serotype 1 infection and usually do not have time to treat them. App serotype 2 has been detected more and more recently and has also become the main pathogen (Ohba et al, 2010;Sarkozi, Makrai, & Fodor, 2018). In the event of an acute outbreak of App, it can be treated with tilmicosin injection (Papatsiros et al, 2018), but if it occurs on a large scale, the injection will greatly increase the cost and require a large amount of labour.…”
Section: Discussionmentioning
confidence: 99%
“…Serotypes 1, 5 and 7 are the predominant serotypes found in North America while serotype 2 is the predominant serotype in many European countries (Chiers et al, 2010;Kim et al, 2010). The clinical signs of the disease can be hyperacute, acute or chronic Ohba et al, 2010). Chronic porcine pleuropneumonia is usually very contagious because the bacteria persist in the lungs, the tonsils and, in rare cases, the nasal cavity.…”
Section: Introductionmentioning
confidence: 99%